Distribution of Nutrient Matters in Saline Lakes in the Dry Valleys, South Victoria Land, Antarctica - Shyu NAKAYA; Tetsuya TORII; Noboru YAMAGATA (National Institute of Polar Research, 1977)
The distribution of nutrient matters in the saline lakes in the Dry Valleys was studied on the spot in the summers 1971-1972 and 1972-1973. The presence of a large amount of nitrogen compounds in the saline lakes was pointed out and their source was discussed together with the distribution pattern of the respective nitrogen compound in the lake water. Most of the nutrient matters were probably supplied by the melt water from the adjacent glaciers and by the decomposed organic matters in the bottom sediments of each lake.